2016
DOI: 10.3390/ijerph13030248
|View full text |Cite
|
Sign up to set email alerts
|

Importance of Macrophyte Quality in Determining Life-History Traits of the Apple Snails Pomacea canaliculata: Implications for Bottom-Up Management of an Invasive Herbivorous Pest in Constructed Wetlands

Abstract: Pomacea canaliculata (Ampullariidae) has extensively invaded most Asian constructed wetlands and its massive herbivory of macrophytes has become a major cause of ecosystem dysfunctioning of these restored habitats. We conducted non-choice laboratory feeding experiments of P. canaliculata using five common macrophyte species in constructed wetlands including Ipomoea aquatica, Commelina communis, Nymphoides coreana, Acorus calamus and Phragmites australis. Effects of macrophytes on snail feeding, growth and fecu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…Vegetation plays a crucial role in the pollutant removal process; hence, the plants selected must be able to adapt to the conditions of the CWs and must be suitable for the removal of pollutants. However, it is a subject that has been little studied in tropical and intertropical areas [20]. Generally, the plants used in CWs are macrophytes typical of natural wetlands, such as Phragmites australis and species of the Typha , Scirpus , and Cyperus genera [6].…”
Section: Introductionmentioning
confidence: 99%
“…Vegetation plays a crucial role in the pollutant removal process; hence, the plants selected must be able to adapt to the conditions of the CWs and must be suitable for the removal of pollutants. However, it is a subject that has been little studied in tropical and intertropical areas [20]. Generally, the plants used in CWs are macrophytes typical of natural wetlands, such as Phragmites australis and species of the Typha , Scirpus , and Cyperus genera [6].…”
Section: Introductionmentioning
confidence: 99%
“…A study by Qiu & Kwong (2009) also revealed that P. canaliculata that consumed I. aquatica grew much faster than when feeding on the other plant species. The study by Yam et al (2016) also found that the snails consumed more Nymphoides coreana than Commelina communis but, surprisingly, the snails grew at an equal rate. In another feeding study, P. canaliculata consumed more of the macrophyte Egeria najas than Ceratophyllum demersum but snails fed on C. demersum grew much faster than those fed on E. najas (Cruz et al, 2015).…”
Section: Feeding Consumption and Growth Rate Of Juveniles Fed On Individual Macrophytesmentioning
confidence: 86%
“…Qiu and Kwong (2009) and Yam et al. (2016) also found plant N and P contents to be important for enhancing palatability, supporting growth and offspring quantity of apple snails. However, it should be noted that the snail growth might also be influenced by the available plant quantity in our experiment, since plant biomass in moderate nutrient treatment was higher than in low nutrient treatment.…”
Section: Discussionmentioning
confidence: 98%